Nuclear Reactions : How Nuclear-Armed States Behave - Bell, Mark (Researcher) (Book collections on Project MUSE., 2021)
"This book examines the ways in which states change their foreign policies when they acquire nuclear weapons, using case studies of the United Kingdom, South Africa, and the United States"--